ANALISIS PERENCANAAN KEBUTUHAN ALAT KESEHATAN DENGAN METODE EOQ DI PUSKESMAS CILEUNGSI TAHUN 2022 - Diyah Sufi Nashtiti, (2022)
Planning activities are carried out to be able to overcome or avoid shortages of medical devices by using accountable methods. The purpose of this study was to analyze the planning of medical equipment that needs to be available when needed with the EOQ method at the Cileungsi Health Center. This research design is descriptive qualitative. Methods of collecting data by conducting interviews with informants and reviewing documents. Data validation was carried out using triangulation methods and triangulation of informants in this study was determined directly using the purposive sampling method, totaling 3 people consisting of the Head of Public Health Center, Head of Logistics, and Logistics Staff. For the number of orders for goods, the EOQ calculation is smaller than the calculation carried out by the health center and the frequency of orders is calculated by the calculation carried out by the health center. By doing calculations with the EOQ method, it is possible to economize the costs that will be incurred to carry out inventory and procurement of goods more efficiently than the calculations carried out by the health center.